Analysis of the expansion process of cracks caused by blasting stress waves in a PMMA medium with filled defects. (June 2021) - Wang, Yanbing; Dong, Jiaqing; Wang, Zhaoyang; Zhao, Yabin
Highlights: Crack expansion in PMMA under blastload was conducted. Experiment was effectively inverted using DLSM model. Studied the influence factors. Abstract: The occurrence of defects in a medium has a significant role in the transmission of blasting stress waves and the expansion of blast-caused cracks. In this study, an experiment is first conducted on the crack expansion in a polymethyl methacrylate (PMMA) medium with vertically filled defects under a blasting load by using the digital laser dynamic caustics (DLDC) testing system. The origin, expansion, and termination of wing cracks are analyzed, and the variation of the dynamic stress intensity factor and the crack expansion velocity on the crack tip are studied. An effective inversion to the stress wave transmission and the crack expansion is achieved via a test conducted using the distinct lattice spring model (DLSM), along with a comparison between the stress variation at the center points on the wave heading side, back side, and endpoints of the defect. The characteristics of the impact due to the stress wave are also analyzed. Lastly, the expansion velocity/acceleration difference between the wing cracks are analyzed and compared with various defect characteristics (filled, open, closed, bedding).